Sulfated Metabolites of Flavonolignans and 2,3-Dehydroflavonolignans: Preparation and Properties - Valentová, Kateřina; Purchartová, Kateřina; Rydlová, Lenka; Roubalová, Lenka; Biedermann, David; Petrásková, Lucie; Křenková, Alena; Pelantová, Helena; Holečková-Moravcová, Veronika; Tesařová, Eva; Cvačka, Josef; Vrba, Jiří; et al. (International journal of molecular sciences, 2018)
Silymarin, an extract from milk thistle (Silybum marianum) fruits, is consumed in various food supplements. The metabolism of silymarin flavonolignans in mammals is complex, the exact structure of their metabolites still remains partly unclear and standards are not commercially available. This work is focused on the preparation of sulfated metabolites of silymarin flavonolignans. Sulfated flavonolignans were prepared using aryl sulfotransferase from Desulfitobacterium hafniense and p-nitrophenyl sulfate as a sulfate donor and characterized by high-resolution mass spectrometry (HRMS) and nuclear magnetic resonance (NMR). Their 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and N,N-dimethyl-p-phenylenediamine (DMPD) radical scavenging; ferric (FRAP) and Folin⁻Ciocalteu reagent (FCR) reducing activity; anti-lipoperoxidant potential; and effect on the nuclear erythroid 2-related factor 2 (Nrf2) signaling pathway were examined. Pure silybin A 20-O-sulfate, silybin B 20-O-sulfate, 2,3-dehydrosilybin-20-O-sulfate, 2,3-dehydrosilybin-7,20-di-O-sulfate, silychristin-19-O-sulfate, 2,3-dehydrosilychristin-19-O-sulfate, and silydianin-19-O-sulfate were prepared and fully characterized. Sulfated 2,3-dehydroderivatives were more active in FCR and FRAP assays than the parent compounds, and remaining sulfates were less active chemoprotectants. The sulfated flavonolignans obtained can be now used as authentic standards for in vivo metabolic experiments and for further research on their biological activity.
Keywords: Free Radical Scavengers; Antioxidants; flavonolignany; Dietary Supplements; Silybum marianum; Molecular Structure; Sulfates; sírany; potravní doplňky; Fruit; hmotnostní spektrometrie; ostropestřec mariánský; rostliny; ovoce; magnetická rezonanční spektroskopie; molekulární struktura; scavengery volných radikálů; antioxidancia; Mass Spectrometry; Plants; Magnetic Resonance Spectroscopy; Flavonolignans